A defined method for differentiating human iPSCs into midbrain dopaminergic progenitors that safely restore motor deficits in Parkinson’s disease - Nakamura, Ryota; Nonaka, Risa; Oyama, Genko; Jo, Takayuki; Kamo, Hikaru; Nuermaimaiti, Maierdanjiang; Akamatsu, Wado; Ishikawa, Kei-ichi; Hattori, Nobutaka (Frontiers in Neuroscience, 2023)
Background Parkinson’s disease (PD) is a progressive neurodegenerative condition that primarily affects motor functions; it is caused by the loss of midbrain dopaminergic (mDA) neurons. The therapeutic effects of transplanting human-induced pluripotent stem cell (iPSC)-derived mDA neural progenitor cells in animal PD models are known and are being evaluated in an ongoing clinical trial. However, However, improvements in the safety and efficiency of differentiation-inducing methods are crucial for providing a larger scale of cell therapy studies. This study aimed to investigate the usefulness of dopaminergic progenitor cells derived from human iPSCs by our previously reported method, which promotes differentiation and neuronal maturation by treating iPSCs with three inhibitors at the start of induction. Methods Healthy subject-derived iPS cells were induced into mDA progenitor cells by the CTraS-mediated method we previously reported, and their proprieties and dopaminergic differentiation efficiency were examined in vitro. Then, the induced mDA progenitors were transplanted into 6-hydroxydopamine-lesioned PD model mice, and their efficacy in improving motor function, cell viability, and differentiation ability in vivo was evaluated for 16 weeks. Results Approximately ≥80% of cells induced by this method without sorting expressed mDA progenitor markers and differentiated primarily into A9 dopaminergic neurons in vitro. After transplantation in 6-hydroxydopamine-lesioned PD model mice, more than 90% of the engrafted cells differentiated into the lineage of mDA neurons, and approximately 15% developed into mature mDA neurons without tumour formation. The grafted PD model mice also demonstrated significantly improved motor functions. Conclusion This study suggests that the differentiation protocol for the preparation of mDA progenitors is a promising option for cell therapy in patients with PD.